Step-by-step therapy with chondroitin sulfate in patients with osteoarthritis in an outpatient setting - L. V. Vasilyeva; E. F. Evstratova; A. V. Nikitin; N. S. Burdina; N. A. Barsukova (Современная ревматология)
Objective: to evaluate the efficiency of different chondroitin sulfate (CS) treatment regimens in patients with osteoarthritis (OA).Patients and methods. The investigation enrolled 44 patients of both sexes aged 48.6±6.4 years with knee OA. 26 patients of a study group received step-by-step CS (chondrogard and structum)-containing therapy in combination with magnetic laser therapy (low-intensity laser radiation (LILR)) for the affected joints. 18 patients of a comparison group had traditional treatment with nonsteroidal anti-inflammatory drugs and physiotherapy.Results. Step-by-step therapy with chondrogard in combination with LILR has an advantage over the traditional treatment regimen, because it is characterized by more pronounced long-acting analgesic and anti-inflammatory effects and by the absence of adverse reactions.